Context Potential Ionic Liquid on Improving the Mechanical Properties of Bamboo for ESD-Loaded Learning at Universities - Fadhilah, Anita; Hernani, Hernani; Hanafi, Ainul Ahmadsyah (JURNAL PENDIDIKAN SAINS (JPS), 2025)
Ionic liquids, known for their environmental friendliness and potential to enhance bamboo's mechanical properties, align with several SDGs, including No Poverty, Quality Education, and Climate Action. This study explores the potential of ionic liquids in improving bamboo's mechanical properties and integrating Environmental Sustainability and Development (ESD) into chemistry education. Data from 36 chemistry students revealed a lack of understanding among prospective teachers about ESD and its connection to ionic liquids and chemistry concepts. However, students recognized the sustainability potential of ionic liquids and agreed on incorporating these contexts into their learning. These findings highlight the need to further integrate ESD into chemistry education, emphasizing ionic liquids and their role in sustainable practices like bamboo processing.